PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA PICK THE FRIES UNTUK MENINKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS IV SDN 05 GEDANGAN - Revianti, Reka; Kusumaningrum, Diana (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2025)
ABSTRACT Critical thinking skills are essential for students to have, but in reality, these skills are still relatively low. This is reflected in the fourth grade students of SDN 05 Gedangan who, when given questions by the teacher, tend to provide answers based on the available textbooks or theme books, without going through further analysis. The purpose of this study was to reveal the extent to which the application of the Team Games Tournament (TGT) learning model supported by Pick the Fries media was able to improve the critical thinking skills of fourth grade students of SDN 05 Gedangan. The type of research used was Classroom Action Research (CAR) with a qualitative descriptive technique consisting of two cycles. Based on the results of the study, the application of the Team Games Tournament (TGT) learning model assisted by Pick the Fries media was proven effective in improving the critical thinking skills of fourth grade students at SDN 05 Gedangan. The increase is seen from the percentage of each indicator, critical thinking from 36% to 72%, analyzing information from 44% to 72%, using data to develop important insights from 29% to 76%, and synthesizing multiple perspectives from 38% to 72%. The increase in classical cycles I and II, there was an increase from 20% (low cognitive level category to 85% (very high cognitive level category). Keywords: Team Games Tournament (TGT) Model, Critical Thinking Skills, Indonesian Language.